Kerjasama Indonesia-Australia Dalam Menanggulangi Illegal, Unreported, Unregulated Fishing Di Laut Timor Australia Tahun 2017-2021 - Chenika Fricila; R. Dudy Heryadi; Dairatul Ma’arif (Global Political Studies Journal, 2022)
Indonesia and Australia are two partner countries that are actively cooperating in the fisheries sector with the aim of tackling IUU fishing. Despite that both countries have taken many approaches and policies, the number of IUU fishing case is still remain high. One area that is vulnerable to these activities is the Australian Timor Sea because of its direct adjacent to the Indonesian sea. This research was conducted with the aim of knowing whether the realization of the cooperation that has been implemented has succeeded in reducing the transnational crime of IUU fishing that occurred in the Australian Timor Sea. This study uses qualitative approach and descriptive type of research that uses two data sources, namely primary and secondary. In analysing this research, the author uses bilateral cooperation theory, maritime security and IUU fishing concept. The results of this study indicated that the realization of the cooperation that has been carried out by Indonesia and Australia in the fisheries sector as an effort to tackle IUU fishing in 2017-2021 has not been able to reduce IUU fishing cases in Australian Timor Sea Australia because of the economic factors of Indonesian fishermen who are affected by the COVID-19 pandemic. Keywords: Australia, Australian Timor Sea, Fisheries cooperation, Indonesia, IUU fishing.